Efficacy of Thromboelastography (TEG) in Predicting Acute Trauma-Induced Coagulopathy (ATIC) in Isolated Severe Traumatic Brain Injury (iSTBI) - Albert, Venencia (Indian J Hematol Blood Transfus, 2018)
To evaluate the efficacy of point-of-care thromboelastography (TEG) to predict acute trauma-induced coagulopathy (ATIC) in isolated severe TBI (iSTBI). We conducted an observational diagnostic cohort. Patients for whom TEG was performed before blood transfusion were stratified by conventional coagulation tests (CCTs) on admission and classified as “ATIC” (prothrombin time ≥ 16.70 s; international normalized ratio ≥ 1.27; activated partial thromboplastin time ≥ 28.80 s) (n = 24) or “no ATIC” (n = 34). Univariate analysis to compare groups, receiver operating characteristic analysis to establish cut-off and diagnostic validation was done. Fifty-eight patients were included [32(25–45) years; 97% male; GCS 6.3 ± 1.5]. 41% developed ATIC. Compared to no-ATIC, ATIC group had significantly prolonged κ-time (4.6 vs. 2.5 min; p = 0.01) and shortened α-angle (40.2° vs. 56.3°; p = 0.03). A cut-off for κ-time ≥ 3.7 (AUC 0.68 95% CI 0.54–0.82, specificity 70%, sensitivity 63%) and α angle ≤ 48.0 (AUC 0.66, 95% CI 0.51–0.81, specificity 67%, sensitivity 67%) was established. The diagnostic accuracy of this cut-off for identifying ATIC, was 55.6% with sensitivity (81.8%) and specificity (14.3%). TEG may be a clinically sensitive test for identifying the underlying coagulopathy following TBI. However confirmation with CCTs is recommended.